Differential SLC1A2 Promoter Methylation in Bipolar Disorder With or Without Addiction - Jia, Yun-Fang; Choi, YuBin; Ayers-Ringler, Jennifer R.; Biernacka, Joanna M.; Geske, Jennifer R.; Lindberg, Daniel R.; McElroy, Susan L.; Frye, Mark A.; Choi, Doo-Sup; Veldic, Marin (Frontiers in Cellular Neuroscience, 2017)
While downregulation of excitatory amino acid transporter 2 (EAAT2), the main transporter removing glutamate from the synapse, has been recognized in bipolar disorder (BD), the underlying mechanisms of downregulation have not been elucidated. BD is influenced by environmental factors, which may, via epigenetic modulation of gene expression, differentially affect illness presentation. This study thus focused on epigenetic DNA methylation regulation of SLC1A2, encoding for EAAT2, in BD with variable environmental influences of addiction. High resolution melting PCR (HRM-PCR) and thymine-adenine (TA) cloning with sequence analysis were conducted to examine methylation of the promoter region of the SLC1A2. DNA was isolated from blood samples drawn from BD patients (n=150) with or without addiction to alcohol, nicotine, or food , defined as binge eating, and matched controls (n=32). In comparison to controls, the SLC1A2 promoter region was hypermethylated in BD without addiction but was hypomethylated in BD with addiction. After adjusting for age and sex, the association of methylation levels with nicotine addiction (p=0.0009) and BE (p=0.0002) remained significant. Consistent with HRM-PCR, direct sequencing revealed increased methylation in CpG site 6 in BD, but decreased methylation in 4 CpG sites (3, 6, 48, 156) in BD with alcohol and nicotine addictions. These results suggest that individual point methylation within the SLC1A2 promoter region may be modified by exogenous addiction and may have a potential for developing clinically valuable epigenetic biomarkers for BD diagnosis and monitoring.